Ar-Act-Count-Think (accounting fun board) / Abd Rahim Mohd Aris ... [et al.] - Mohd Aris, Abd Rahim; Abdullah, Zuhaizi; Umanan, Farhana; Abdullah, Noor Asmahan; Adri, Juliana (2020)
Accounting Fun Board is an innovative teaching material that aims to help students specifically in remembering, mastering, and understanding the classification of accounts in the topic of Accounting Equations. The adoption of this product mainly focuses on students who do not have any basic knowledge of accounting courses. Accounting Fun Board is in a form of an interactive game that is compatible with 21st century-oriented education. Basically, this application entails the use of a synergistic game method which is applied to the concept of Augmented Reality (AR). In terms of the sampling frame, this study was conducted on 59 students who enrolled in the Accounting Matriculation Program Semester 1 session 2019/2020 and do not have any basic knowledge of the accounting course. As a result, the findings found that 67.9% of the treatment group got A and A- compared to 25.8% of the control group through pre and post questions. Hence, it clearly proved that students are more prepared, and learning is more student-centered by applying this application. In addition, students are more understanding and easier to remember the syllabus. Furthermore, it also can be used repeatedly by enticing them in utilizing gadgets such as a mobile phone as an instrument.